The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1021/jf025554v
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Various Phosphopeptides of Caseins on Iron Absorption

Abstract: The influence of the origin and kind of caseinophosphopeptide (CPP) on iron absorption was assessed by comparing a commercially available CPP mixture (CPPs) and derived chromatographic fractions with the purified, chemically phosphopeptide of beta-casein [beta-CN(1-25)] using a perfused rat duodenal loop system; gluconate iron was used as control. Only iron complexed to beta-CN(1-25) displayed a better bioavailability than gluconate iron. The results obtained with various chromatographic fractions indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 19 publications
1
61
1
3
Order By: Relevance
“…New studies have shown that the CPPs are a mixture of peptides with different molecular masses in the range from 1.4 to 9.6kDa and that about 50% of the CPPs identified presented the sequence (SerPSerP-SerP-Glu-Glu), responsible for the property of binding minerals [80]. In addition to increasing the solubility, absorption, and fixation of minerals to bones and teeth, the CPPs along with the caseinoglycomacropeptide (GMP) also act by inhibiting the adherence of Streptococcus sobrinus and S. mutans, thus decreasing the incidence of tooth decay and dental erosion [81].…”
Section: Caseinophosphopeptides (Cpps) and Glycomacropeptide (Gmp)mentioning
confidence: 99%
See 1 more Smart Citation
“…New studies have shown that the CPPs are a mixture of peptides with different molecular masses in the range from 1.4 to 9.6kDa and that about 50% of the CPPs identified presented the sequence (SerPSerP-SerP-Glu-Glu), responsible for the property of binding minerals [80]. In addition to increasing the solubility, absorption, and fixation of minerals to bones and teeth, the CPPs along with the caseinoglycomacropeptide (GMP) also act by inhibiting the adherence of Streptococcus sobrinus and S. mutans, thus decreasing the incidence of tooth decay and dental erosion [81].…”
Section: Caseinophosphopeptides (Cpps) and Glycomacropeptide (Gmp)mentioning
confidence: 99%
“…These peptides presented high phosphoserine content and were capable of increasing the calcium balance by 39% to 70% in newborn children with rickets. Later studies showed that the CPPs could also bind, in addition to Ca, otherminerals like Mg, Fe, Ba, Cr, Ni, Co, and Se [78,79].New studies have shown that the CPPs are a mixture of peptides with different molecular masses in the range from 1.4 to 9.6kDa and that about 50% of the CPPs identified presented the sequence (SerPSerP-SerP-Glu-Glu), responsible for the property of binding minerals [80]. In addition to increasing the solubility, absorption, and fixation of minerals to bones and teeth, the CPPs along with the caseinoglycomacropeptide (GMP) also act by inhibiting the adherence of Streptococcus sobrinus and S. mutans, thus decreasing the incidence of tooth decay and dental erosion [81].…”
mentioning
confidence: 99%
“…The reviews describe randomised controlled trials investigating the effect of iron supplementation on prevention of iron deficiency and on haemoglobin concentrations in infants and young children (Iannotti et al, 2006;Gera et al, 2007). The applicant also provided in vitro and animal studies (Bouhallab et al, 2002;Etcheverry et al, 2004a, b;Kibangou et al, 2005;Rohner et al, 2007), three extracts from textbooks in German and six reports/papers from scientific bodies as being pertinent to the health claim (IoM, 2001;Aggett et al, 2002;INACG, 2002;JHCI, 2003;FAO/WHO, 2004;DGE, 2008).…”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 99%
“…This is of nutritional interest because of the importance of iron in human health. In addition, in vitro availability of iron bound to casein phosphopeptides and net absorption of iron in animals perfused with β-caseinophosphopeptide (f1-25) are high as a result of the increase in the solubility of iron bound to Antioxidant activity of β-casein hydrolysate 451 the peptides [1,9,48,59]. The phosphorylated groups of casein may also play an important role in regulating the oxidation state of iron [15] and the subsequent development of lipid oxidation.…”
Section: Introductionmentioning
confidence: 99%